Stroop interference in a delayed match-to-sample task: evidence for semantic competition - Sturz, Bradley R.; Green, Marshall L.; Locker, Lawrence; Boyer, Ty W. (Frontiers in Psychology, 2013)
Discussions of the source of the Stroop interference effect continue to pervade the literature. Semantic competition posits that interference results from competing semantic activation of word and color dimensions of the stimulus prior to response selection. Response competition posits that interference results from competing responses for articulating the word dimension vs. the color dimension at the time of response selection. We embedded Stroop stimuli into a delayed match-to-sample (DMTS) task in an attempt to test semantic and response competition accounts of the interference effect. Participants viewed a sample color word in black or colored fonts that were congruent or incongruent with respect to the color word itself. After a 5 s delay, participants were presented with two targets (i.e., a match and a foil) and were instructed to select the correct match. We probed each dimension independently during target presentations via color targets (i.e., two colors) or word targets (i.e., two words) and manipulated whether the semantic content of the foil was related to the semantic content of the irrelevant sample dimension (e.g., word sample “red” in blue font with the word “red” as the match and the word “blue” as the foil). We provide evidence for Stroop interference such that response times (RTs) increased for incongruent trials even in the presence of a response option with semantic content unrelated to the semantic content of the irrelevant sample dimension. Accuracy also deteriorated during the related foil trials. A follow-up experiment with a 10 s delay between sample and targets replicated the results. Results appear to provide converging evidence for Stroop interference in a DMTS task in a manner that is consistent with an explanation based upon semantic competition and inconsistent with an explanation based upon response competition.